(3GdQhVI GdfOjI aj TQM GdJMaI GdYdhjIs - (3eMeO Hf ESeGYjd Hf UdGM Hf eMeO GdMSfj, GdcMdGfj Ke GdUfYGfj, CHh EHQGgje, YR GdOjf, GdeYQha cCSdGag HGdCejQ, J (B1182 (3g` s; (3GdUfYGfj , eMeO Hf ESeGYjd Hf UdGM Hf eMeO GdMSfj GdcMdGfj, YR GdOjf CHh EHQGgje,J (B1182 (3g` s
(3ChdgG (B:s
(3JMaI JgOi def jghi YdjgG ef Qbi TChG ef GdeLO YdjG s
(3BNQgG (B:s
(3UdhGJ Gddg JJQi dgeG hYdi GdBd UHGMkG hYTjkG s
(3hgj bUjOI ai eOM CejQ GdeDefjf Ydi Hf CHj WGdH hTQMgGs
(3hjdjgG ef GdfSNI GdCes
(3hYdjgG eWGdYI SfI (B1324(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs